High altitude accumulation and preserved climate information in the western Pamir, observations from the Fedchenko Glacier accumulation basin. Issue 256 (27th April 2020) - Lambrecht, Astrid; Mayer, Christoph; Bohleber, Pascal; Aizen, Vladimir
Abstract: The accumulation region of Fedchenko Glacier represents an extensive snow reservoir in the Pamir Mountains feeding the longest glacier in Central Asia. Observed elevation changes indicate a continuous ice loss in the ablation region of Fedchenko Glacier since 1928, while the mass balance of the accumulation region is largely unknown. In this study, we show that accumulation varies considerably in the main accumulation basin, with accumulation rates up to 2400 mm w.e. a −1 in the West, decreasing to <1000 mm w.e. a −1 in the center, although the elevation difference is <200 m. The combination of snow/firn samples and ground-penetrating radar profiles suggests that this accumulation pattern is persistent during the recent past. The recent accumulation history is reconstructed from internal radar reflectors using a firn densification model and shows strong interannual variations, but near constant mean values since 2002. Modeling of trajectories, based on accumulation and glacier geometry, results in an estimate of the depth/age relation close to the main divide. This region provides one of the most suitable locations for retrieving climate information with temporal high resolution for the last millennium, with a potential to cover most of the Holocene in less detail.